Implementasi Program Karya Bakti Di Pangkalan Utama Angkatan Laut V Surabaya - Wibowo, Andik Putro; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2023)
This study aims to determine the implementation of the Karya Bakti program at the Main Naval Base V Surabaya along with its supporting and inhibiting factors. This research is a type of qualitative research with a descriptive approach. The theory used in this study is the theory of policy implementation according to George Edward III, with 4 variables namely communication, resources, disposition and bureaucratic structure. The collection of research data was carried out through observation, interviews, document studies. Furthermore, the data analysis used is data reduction, data presentation, data presentation and drawing conclusions .Rutilahu program at the V Surabaya Main Naval Base in the variables of communication, resources, disposition and bureaucratic structure, showed positive indications in supporting policy implementation, so that it could be implemented properly, although there were several obstacles that could be overcome. ,.Factors supporting the implementation of the Karya Bakti Rutilahu program at the Main Naval Base V Surabaya, namely internal and external communication and coordination of Lantamal V in general have been good, adequate resource support, the attitude of implementers who strongly support the implementation of the program, and the existence of bureaucratic structure and internal chain of command of Lantamal V which can be used in implementing the Rutilahu program. Then, the inhibiting factors for the implementation of the Karya Bakti Rutilahu program at the Main Naval Base V Surabaya, namely there is still a misperception by the recipient community that considers the overall repair of the house and considers that recipients of home renovations do not receive BLT, there is road access that is still not feasible to pass. vehicles transporting building materials and there are still problems with the accuracy of the actual owner’s data of the house to be renovated, the Rutilahu Lantamal program is still limited to the East Java region and there is no collaboration with the Rutilahu program in Lanals in Central Java and Bali Provinces and the implementation of the Rutilahu Lantamal V program still rely on grants from the East Java Provincial Government alone From the results of this study, it is recommended that Lantamal V make an approach to the Central Java and Bali Pempov so that Lantamal V is involved in the Rutilahu program through Lanals in the two regions, involve the Maritime Service Industry to work together in improving the welfare of coastal communities through the Rutilahu program, take an approach to maritime service companies to be involved in financing the Rutilahu program. Clarify transportation support for the transportation of home improvement materials that have to travel through difficult roads Keywords : Program implementation, uninhabitable residential houses, Main Naval Base V